DETERMINAN PENGARUH PENGAMBILAN KEPUTUSAN PEMBELIAN PERUMAHAN NON MBR DI KABUPATEN SLEMAN - Khoirudin, Rifki; Khasanah, Uswatun; Zakiyyah, Nurul Azizah Az (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
House is one of the basic needs other than food and shelter. The high demand for housing in Sleman Regency is an opportunity for housing developers. especially for non-low-income housing. The purpose of this study was to analyze the determinants of purchasing decisions for non-MBR housing in Sleman Regency. The research method used is multiple linear regression analysis. statistical methods and econometrics. The analysis tool used is SPSS 25.0. The research data used is primary data with the type of cross section data. Samples were taken from 14 housing located in Sleman Regency. The number of respondents in this study were 82 respondents who were taken from 14 housing estates in Sleman Regency with the method of determining the number of samples based on the Slovin formula. The sampling method using random sampling. The results of the study conclude that simultaneously all independent variables have an effect on the decision making of purchasing non-MBR housing. Partially, the variable price level suitability, location, facilities and product quality has a positive and significant effect on purchasing decisions for non-MBR housing.